Assessment of the Quality of Injectable Antibiotics in Benin - YEMOA, Achille (My University, 2022)
Abstract. Substandard and falsiﬁed medicines are an enormous threat to global health. Poor quality antibiotic preparations contribute to the development of antimicrobial resistance. In surgery, where the occurrence of healthcareassociated infections is high, healthcare teams need to rely on the quality of antibiotic prophylaxis to prevent infections. We assessed the quality of antibiotics used for surgical infection prophylaxis in Benin. Thirty-three samples were collected from six hospitals located in various departments in Benin. The antibiotics (powders for injection: amoxicillin 1 clavulanic acid, ampicillin, ceftriaxone; solutions for injection: ciproﬂoxacin, gentamicin, metronidazole) were assessed using visual inspection, pharmacotechnical tests (including uniformity of mass, pH measure, sterility test, and active pharmaceutical ingredient identiﬁcation), and assay tests (including a simple analytical method thin layer chromatography) and complex analytical techniques (ultraviolet-visible spectrophotometry, high-performance liquid chromatography—diode-array detec- tion, conductometry). Because the material needed for the methods recommended by the pharmacopeias to assess the dosage of gentamicin was not available, we developed and validated a conductometry method. Results showed that 97% (n 5 32) of the samples passed visual inspection; 100% (n 5 33) of the samples passed the pharmacotechnical tests, identiﬁcation of active ingredients, and sterility test; 88% (n 5 29) passed the test for percentage of active pharmaceutical ingredients. Overall, 15% of the samples did not pass the quality test (3% on visual inspection and 12% for excess active ingredients). Although most of the samples passed the quality tests, it appears important to perform routine quality control for intravenous medicines.
Keywords: Assessment; Quality; Injectable Antibiotics; Benin